Genomics and pathogenesis of the avian coronavirus infectious bronchitis virus - Quinteros, JA; Noormohammadi, AH; Lee, SW; Browning, GF; Diaz-Méndez, A (My University, 2022)
Infectious bronchitis virus (IBV) is a member of the family Coronaviridae, together with viruses such as SARS-CoV, MERS-CoV and SARS-CoV-2 (the causative agent of the COVID-19 global pandemic). In this family of viruses, interspecies transmission has been reported, so understanding their pathobiology could lead to a better understanding of the emergence of new serotypes. IBV possesses a single-stranded, non-segmented RNA genome about 27.6 kb in length that encodes several non-structural and structural proteins. Most functions of these proteins have been confirmed in IBV, but some other proposed functions have been based on research conducted on other members of the family Coronaviridae. IBV has variable tissue tropism depending on the strain, and can affect the respiratory, reproductive, or urinary tracts; however, IBV can also replicate in other organs. Additionally, the pathogenicity of IBV is also variable, with some strains causing only mild clinical signs, while infection with others results in high mortality rates in chickens. This paper extensively and comprehensibly reviews general aspects of coronaviruses and, more specifically, IBV, with emphasis on protein functions and pathogenesis. The pathogenicity of the Australian strains of IBV is also reviewed, describing the variability between the different groups of strains, from the classical to the novel and recombinant strains. Reverse genetic systems, cloning and cell culture growth techniques applicable to IBV are also reviewed.
Keywords: Avian coronavirus; Cloning; Genetics; IBV; Infectious bronchitis; Pathogenesis; Protein functions